Marks on late medieval barrels from the southern Baltic coast - Maciej Miścicki (Archeologické Rozhledy, 2025)
In late medieval trade, barrels were the most popular containers for transporting various commodities. They were often marked with various symbols, the meaning of which is difficult to interpret. The presented analysis included 112 fragments of barrels with carved or branded marks. All the specimens were dated between the 14th and 16th centuries AD and came from archaeological excavations in Elbląg, Gdańsk, and Puck. The investigated symbols are thought to have served different functions, including as merchants’, craftsmen’s, or ownership marks. The registered examples were divided into five groups: branded; compositions of multiple irregular lines; geometric figures; simple compact, often symmetrical symbols; and other that do not belong to any of the aforementioned categories. Analyses of the investigated artefacts and their comparisons with other published finds and written accounts revealed that simple compact marks were applied on barrels used in mercantile contexts. Determining the function of barrels based on marks of the other groups was proved to be ambiguous and requires further research.